Local Fractional Operator for a One-Dimensional Coupled Burger Equation of Non-Integer Time Order Parameter - Sunday O. Edeki; Grace O. Akinlabi (Institute for Research and Community Services (LPPM) ITB, 2018)
In this study, approximate solutions of a system of time-fractional coupled Burger equations were obtained by means of a local fractional operator (LFO) in the sense of the Caputo derivative. The LFO technique was built on the basis of the standard differential transform method (DTM). Illustrative examples used in demonstrating the effectiveness and robustness of the proposed method show that the solution method is very efficient and reliable as